-4(x-4)+6=22

Simple and best practice solution for -4(x-4)+6=22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(x-4)+6=22 equation:


Simplifying
-4(x + -4) + 6 = 22

Reorder the terms:
-4(-4 + x) + 6 = 22
(-4 * -4 + x * -4) + 6 = 22
(16 + -4x) + 6 = 22

Reorder the terms:
16 + 6 + -4x = 22

Combine like terms: 16 + 6 = 22
22 + -4x = 22

Add '-22' to each side of the equation.
22 + -22 + -4x = 22 + -22

Combine like terms: 22 + -22 = 0
0 + -4x = 22 + -22
-4x = 22 + -22

Combine like terms: 22 + -22 = 0
-4x = 0

Solving
-4x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-4'.
x = 0

Simplifying
x = 0

See similar equations:

| 12b-5c+5b+1= | | 16x+3y= | | 3[4+2(y-1)]=36 | | -4x+90=50 | | 7=5+2(7c+1) | | 4-12=5s+51 | | (50-2x)*x=200 | | (7+2)xX+1= | | 5x+61=73+2x | | -g=1.5g-3 | | m(x)=(3x-1)(3-x)+4x^3+19 | | y=(20+x)(3000-100x) | | -0.75x=0.86 | | (3-9x)= | | 3=4-3(5c-1) | | 20+10m=200 | | 5b-14-3b=30 | | 15-5x=26 | | 6x+7x=16 | | 2x-2=4(x-1) | | 9a+3a+12=36 | | -5+7(k+6)=93 | | 6(-p)=54 | | x^2+4x+2=5x+7 | | -2m+19= | | 35+80h=915 | | 73-17=46+7 | | -9(8-9m+n)= | | 3x^3-4x^3= | | -4(7v-7)+5v=-87 | | 2x^2-20x+100=108 | | 5x+3y+2z=4 |

Equations solver categories